Rethinking Sustainability Towards a Regenerative Economy - Andreucci, Maria Beatrice; Marvuglia, Antonino; Baltov, Milen; Hansen, Preben (Future City, 2021)
This open access book is based on work from the COST Action "RESTORE - REthinking Sustainability TOwards a Regenerative Economy'', and highlights how sustainability in buildings, facilities and urban governance is crucial for a future that is socially just, ecologically restorative, and economically viable, for Europe and the whole planet. In light of the search for fair solutions to the climate crisis, the authors outline the urgency for the built environment sector to implement adaptation and mitigation strategies, as well as a just transition. As shown in the chapters, this can be done by applying a broader framework that enriches places, people, ecology, culture, and climate, at the core of the design task - with a particular emphasis on the benefits towards health and resilient business practices. This book is one step on the way to a paradigm shift towards restorative sustainability for new and existing buildings. The authors want to promote forward thinking and multidisciplinary knowledge, leading to solutions that celebrate the richness of design creativity. In this vision, cities of the future will enhance users' experience, health and wellbeing inside and outside of buildings, while reconciling anthropic ecosystems and nature. A valuable resource for scientists and students in environmental sciences and architecture, as well as policy makers, practitioners and investors in urban and regional development.